Langhian rays (Chondrichthyes, Batomorphii) from Brielas, Lower Tagus Basin, Portugal - FIALHO, Pedro (2019)
The Langhian Vc unit of Brielas section (Caparica road, Almada), in the marine Miocene of the Lower Tagus Basin (West Portugal), is rich in batoid species. In this study, batoids are represented by 149 isolated fossil teeth and a single fossil dental plate collected from a bulk sample of washed and sorted sediment. A total of 12 species belonging to the orders Rhinopristiformes, Rajiformes, Torpediniformes and Myliobatiformes were identified. All genera and some species are known to have extant representatives. Aetobatus cappettai antunes and balbino, 2006, is described now from Langhian material which suggests it is older than previously supposed. The biogeographic ranges, environmental constraints and behaviour of the species described in this study point out to an infralittoral environment characterized by the dominance of warm water conditions, where episodic upwelling contributed to the occurrence of different types of batoids coexisting in the same habitat.